Spatio-Temporal Analysis of Land Cover for Estimating UHI Using GEE in Gorontalo City - La Ode Juni Akbar; Arthur Gani Koto; Ahmad Syamsu Rijal (Postgraduate, University of Mataram, 2025)
This study aims to analyze the spatio-temporal dynamics of land cover for estimating the Urban Heat Island (UHI) phenomenon using Google Earth Engine (GEE) in Gorontalo City.Multi-temporal Landsat 5/7/8/9 data were processed in GEE to derive NDVI, emissivity, and Land Surface Temperature (LST). The UHI index was calculated using the statistical threshold formula UHI = Ts − (μ + 0.5α), where values of zero or below (≤0) indicate non-UHI areas, while positive values (>0) represent areas affected by UHI. A correlation analysis was performed between field temperature, LST, and NDVI. Temporally, Gorontalo City exhibits the expansion and intensification of UHI over the 30-year period. The most evident changes are the increased area of the 0–1 and 1–2 classes enveloping the urban area, while the 2–3 class emerges as localized hotspots corresponding to areas of highest density. LST increased from 21–56 °C (1995) to 26–58 °C (2025), while NDVI declined in the city center but remained high in the southern–western zones and near water bodies. The surface temperature exhibits a strong correlation with vegetation conditions and field temperature. The main drivers of these dynamics were the increase in impervious surface fractions (asphalt/concrete) and the reduction of vegetative cover, which decreased latent heat (evapotranspiration) and increased sensible heat.